Fluorescent Pseudomonas Strains with only Few Plant-Beneficial Properties Are Favored in the Maize Rhizosphere - Vacheron, Jordan; Moënne-Loccoz, Yvan; Dubost, Audrey; Gonçalves-Martins, Maximilien; Muller, Daniel; Prigent-Combaret, Claire (Frontiers in Plant Science, 2016)
Plant Growth-Promoting Rhizobacteria (PGPR) enhance plant health and growth using a variety of traits. Effective PGPR strains typically exhibit multiple plant-beneficial properties, but whether they are better adapted to the rhizosphere than PGPR strains with fewer plant-beneficial properties is unknown. Here, we tested the hypothesis that strains with higher numbers of plant-beneficial properties would be preferentially selected by plant roots. To this end, the co-occurrence of 18 properties involved in enhanced plant nutrition, plant hormone modulation, or pathogen inhibition was analyzed by molecular and biochemical methods in a collection of maize rhizosphere and bulk soil isolates of fluorescent Pseudomonas. Twelve plant-beneficial properties were found among the 698 isolates. Contrarily to expectation, maize preferentially selected pseudomonads with low numbers of plant-beneficial properties (up to five). This selection was not due to the predominance of strains with specific assortments of these properties, or with specific taxonomic status. Therefore, the occurrence of only few plant-beneficial properties appeared favorable for root colonization by pseudomonads.